(untitled) (Research, Society and Development, 2021)
This work aimed to evaluate the effect of applying sewage sludge on the levels of heavy metals and sodium in the soil and in the leaves of sunflower (Helianthus annuus l.). The experiment was performed on Oxisol of the Institute of Agrarian Sciences of the Federal University of Minas Gerais in Montes Claros - MG . Treatment accounted for four doses of sewage sludge of the ETE Montes Claros - MG (0; 10; 20 e 30 t ha-1, in dry basis), with six replications, in randomized block. Have been assessed the levels of Ni, Pb, Cd, Cr, Zn, Cu and Na in soil and plant. The application of doses of up to 30 t ha-1 of sewage sludge in sunflower fertilization did not influence the concentrations of Ni, Pb, Cd, Cr, Zn, Cu and Na in soil and leaf tissue of the plant, with no limitation on agronomical use this waste to the elements mentioned.